Cognitive Model of a SemiMechanized Picking Operation - Martha Caro (Revista Ciencias de la Salud, 2018)
Introduction: The current paper develops a pioneering approach to the human factors of picking operations, which are addressed from a cognitive perspective. Materials and methods: The model thus contributed is established through a qualitative methodology which, based on several theories, is articulated and applied to the real situation of a dry foods company’s semi mechanized picking operation. Results: The results combine the cognitive architecture of the operation and its relations with logistic factors, in order to decrease human error and, therefore, increase service level. Conclusion: the current model provides elements for quantitative modeling, which could include this type of factors in order to optimize the picking operation of a supply chain.